(untitled) (Scientific journal of the Fergana State University, 2024)
Uzbek folk tales are diverse in subject matter. Repetitive, on the one hand, and specific functional combinations of characters and motifs, on the other, have caused the appearance of many new, at the same time, plots that bear a very close resemblance to fairy tales of the peoples of the world, in particular, with such international catalogs as CYC, ATU. But it should be noted that national-territorial, socio-cultural differences are the leading feature of the oral treasury of our people, and this is clearly manifested in every genre expression. A comparative study of any plot or motif can help identify these similarities and differences.